Formal Gold‐to‐Gold Transmetalation of an Alkynyl Group Mediated by Palladium: A Bisalkynyl Gold Complex as a Ligand to Palladium. Issue 38 (6th August 2015) - Toledo, Alberto; Meana, Isabel; Albéniz, Ana C.
Abstract The reaction of [Au(CCn‐Bu)]n with [Pd(η3‐allyl)Cl(PPh3)] results in a ligand and alkynyl rearrangement, and leads to the heterometallic complex [Pd(η3‐allyl)Au(CCn‐Bu)2]2 (3) with an unprecedented bridging bisalkynyl–gold ligand coordinated to palladium. This is a formal gold‐to‐gold transmetalation that occurs through reversible alkynyl transmetalations between gold and palladium.